Coalbed methane potential and coal characteristics in the Lati region, Berau basin, East Kalimantan - Suwarna, Nana; Hermanto, Bambang; Sihombing, Torkis; Kusumah, Kusdji Darwin (Geological Agency, 2006)
http://dx.doi.org/10.17014/ijog.vol1no1.20063aA geological research was performed in the Berau Basin, to provide a better understanding on the potential and resources of coalbed methane (CBM) in Berau Regency, East Kalimantan Province, particularly in the Lati Coalfield. Field observation conducted in the coalfield, shows that the banded to bright banded Lati coal is dominated by the bright banded one. Petrographically, the coal consists of vitrinite comprising typical telocollinite and desmocollinite; with rare to sparse exinite, and minor inertinite, and mineral matter. Geochemical analysis shows the range of volatile matter content is from 32.65–39.60%, total sulfur from 0.35–3.04%, ash varies between 2.78–14.50%, and moisture from 12.23–19.98%. Vitrinite reflectance values (Rv), varying from 0.42–0.57%, tend to indicate that the Lati coal rank ranges from sub-bituminous B to high volatile bituminous C category, with low ash content in general. Moreover, the coal maturity level, thermally immature to early mature, leads to the assumption that the expected gas present is suggested to be of biogenic origin. The fairly well cleated Lati coal shows cleat orientations trending north - northeastward, perpendicular to nearly oblique to the syncline axis. Furthermore, coal microcleat occurs as open tensional, sub-curved to curved lines microcracks, diagonally to perpendicular to bedding plane, but some are parallel to the bedding plane. An in-situ coal gas calculation tends to indicate a low to moderate methane content level, with a value of 44.20–47.08 scf/t. However, the Q1 plus Q2 calculation exhibits the gas content ranging from 41.69 to 78.71 scf/t. Moreover, total calculated gas in-place of the P, Q, and R Seams = 5.33 m3/t = 191.56 scf/t.